Implementasi Scrum Pada Perancangan Sistem Informasi Penyewaan Gedung Di Graha Garda Dirgantara - Rahmi Imanda; Fahmi Abdillah (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
According to its capacity, a building can be used by the general public for various purposes. In thisresearch, the process of renting the building, namely Graha Garda Dirgantara, was still done manually,by going directly to the location. This causes problems for people with busy and hectic schedules. The aimof this research is to create a building rental system that can assist in the transaction process, reportingdata processing, and also marketing. The method used in system design in this research is agilemethodology starting from the product backlog, sprint, daily scrum and sprint review processes. Thisresearch uses the Laravel framework to create a web-based Scrum approach. The results of a surveyconducted using Google Form showed that 53.8 percent of respondents said they strongly agreed and 30.8percent said they agreed. These results also show that this approach makes rental data collection moreefficient because the data collection process has been saved to the database.